Co-pyrolysis of Rice Husk with Underutilized Biomass Species: A Sustainable Route for Production of Precursors for Fuels and Valuable Chemicals - Mohammed, I.Y. (Springer Netherlands, 2017)
In this study, co-pyrolysis of rice husk with underutilized biomass, Napier grass and sago waste was carried out in a fixed bed reactor at 600 °C, 30 °C/min and 5 L/min nitrogen flowrate. Two-phase bio-oil (organic and aqueous) was collected and characterized using standard analytical techniques. 34.13–45.55 wt total boil-oil yield was recorded using assorted biomass compared to pure risk husk biomass with 31.51 wt yield. The organic phase consist mainly benzene derivatives with higher proportion in the oil from the co-pyrolysis process relative to the organic phase from the pyrolysis of the individual biomass while the aqueous phase in all cases was predominantly water, acids, ketones, aldehydes, sugars and traces of phenolics. This study has demonstrated a good approach towards increasing valorization of rice husk in a single reaction step for the production of high grade bio-oil, which can be transformed into fuel and valuable chemicals. © 2016, Springer Science+Business Media Dordrecht.